2023
DOI: 10.1093/jxb/erad081
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione-dependent alarm triggers signalling responses involved in plant acclimation to cadmium

Abstract: Cadmium (Cd) uptake from polluted soils inhibits plant growth and disturbs physiological processes, at least partly due to disturbances in the cellular redox environment. Although the sulfur-containing antioxidant glutathione is important in maintaining redox homeostasis, its role as an antioxidant can be overruled by its involvement in Cd chelation as a phytochelatin precursor. Following Cd exposure, plants rapidly invest in phytochelatin production, thereby disturbing the redox environment by transiently dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…These toxic metals and metalloids are detrimental to plant health and thus may impact general cellular and organellar responses. Iven et al (2023) extend discussion on how GSH and PC pools alter in the event of plant exposure to Cd and influence the ethylene and reactive oxygen species (ROS)-mediated signaling networks. Ramification of stresses imposed by Cd appears to involve ethylene and ROS signaling communicating with mitochondrial retrograde signaling, unfolded protein response, and autophagy.…”
Section: Thiols In Actionmentioning
confidence: 87%
See 1 more Smart Citation
“…These toxic metals and metalloids are detrimental to plant health and thus may impact general cellular and organellar responses. Iven et al (2023) extend discussion on how GSH and PC pools alter in the event of plant exposure to Cd and influence the ethylene and reactive oxygen species (ROS)-mediated signaling networks. Ramification of stresses imposed by Cd appears to involve ethylene and ROS signaling communicating with mitochondrial retrograde signaling, unfolded protein response, and autophagy.…”
Section: Thiols In Actionmentioning
confidence: 87%
“…S 2– and OAS can also modulate the activity of the target of rapamycin (TOR) complex which optimizes plant growth ( Dong et al , 2017 ). Glutathione (γ-glutamylcysteinylglycine; GSH), the tripeptide synthesized from Cys, and Fe–S clusters impact the redox status ( Caubrière et al , 2023 ; Ito and Ohkama-Ohtsu, 2023 ; Iven et al , 2023 ; Pedroletti et al , 2023 ). Sulfation of metabolites and peptides generates 3’-phosphoadenosine-5’-phosphate (PAP), a retrograde signaling molecule communicating messages relevant to a wide spectrum of abiotic stress factors (e.g.…”
mentioning
confidence: 99%
“…After exposure to cadmium, plants quickly allocate resources to produce phytochelatins, which are oligomers of GSH, leading to the disruption of the redox environment by temporarily reducing GSH concentrations. As a result, a cascade of signaling responses is triggered, with ET playing a crucial role in restoring GSH levels [84]. It was recently shown that there is crosstalk between glucosinolate levels and the expression of ET-related genes under S deprivation [85].…”
Section: Ethylene Crosstalk With S Metabolismmentioning
confidence: 99%